Parents' childhood experiences of bonding and parental psychopathology predict borderline personality disorder during adolescence in offspring - Infurna, Maria Rita; Fuchs, Anna; Fischer-Waldschmidt, Gloria; Reichl, Corinna; Holz, Birger; Resch, Franz; Brunner, Romuald; Kaess, Michael (Psychiatry research, 2016)
Previous studies on borderline personality disorder (BPD) development suggest a transgenerational transmission of parent-child relationship quality, which may also be influenced by parents’ mental health status. The aim of this study was twofold. First, we aimed to investigate the transgenerational effect of parental bonding experiences on the development of BPD in their offspring. Second, we examined the association between parents' mental health status and BPD in offspring. Ninety-one female adolescent psychiatric inpatients along with 87 mothers and 59 fathers were enrolled in the study. Adolescent BPD was assessed with the Structured Clinical Interview for DSM-IV-II, parental bonding with the Parental Bonding Instrument, and parents´ psychiatric symptoms with the Patient Health Questionnaire. We found that low parental care produced a transgenerational effect from mother to BPD in offspring. Further, significant associations were found between paternal psychiatric symptoms and adolescent BPD. High paternal stress levels mediated the association between maternal affect reported by fathers and BPD in daughters. There is evidence of a transgenerational effect of parental bonding specifically for female adolescents with BPD, compared with other clinical control subjects. Our findings highlight the importance of including both parents in future research and in early clinical treatment in adolescents with BPD.